Meningkatkan Hasil Belajar IPA Melalui Metode Pembelajaran Guided Inquiry dengan Menggunakan Media Gambar - Meri Finda (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2020)
This study aims to improve science learning outcomes through the guided inquiry-based learning method using image media in class IX-1 students of SMP Negeri 4 Dumai in the 2017/2018 academic year. The subjects of this study were 37 students from Class IX-1 SMP Negeri 4 Dumai, consisting of 11 male students and 26 female students. This research is a classroom action research (PTK) consisting of 2 (two) cycles. The data collection took place from January to February 2018. This research was carried out in different phases, namely the preparation phase, the implementation phase, the observation phase and the reflection phase. The research results showed that the guided research method using image media can improve the scientific learning outcomes of class IX-1 students of SMP Negeri 4 Dumai in the 2017/2018 academic year. Where the average student learning outcomes in the first cycle increased by 83.4 with good categories, in the second cycle to 87.7 with good categories.